Dynamical modeling and simulation of the six-modular high temperature gas-cooled reactor plant HTR-PM600. (15th July 2018) - Dong, Zhe; Pan, Yifei; Zhang, Zuoyi; Dong, Yujie; Huang, Xiaojin
Abstract: The modular high temperature gas-cooled reactor (MHTGR) is a typical small modular reactor (SMR) with inherent nuclear safety, which has a low average power density about 3 MW/m 3, uses TRISO particle based fuel elements, and adopts helium as coolant and graphite as both moderator and structure material. Based upon the multimodular scheme, i.e. multiple MHTGR-based nuclear steam supply system (NSSS) modules driving a single turbine/generator system, the MHTGR-based nuclear power plants (NPPs) with inherent safety as well as any desired power ratings can be realized. However, since multiple NSSS modules are coupled together by the common secondary-circuit, the operation and control of multimodular NPPs is quite different from those classical single modular NPPs. For the design and verification of operation and control strategies of a NPP, it is necessary to develop the dynamical model of this NPP, and to study its open-loop and closed-loop dynamics. In this paper, a lumped-parameter dynamical model of the six-modular MHTGR-based NPP HTR-PM600 is proposed based on the conservation laws of mass, energy and momentum, which is composed of the MHTGR-based NSSS modules and the common secondary-circuit. Then, both the open-loop responses to exterior disturbances and the closed-loop behavior in power-level maneuver are given by numerical simulation, which shows not only the feasibility of this model but also the coupling effect of the modules caused by the common secondary-circuit. Highlights: Modular high temperature reactor (MHTGR) has inherent nuclear safety. Large nuclear plant can be developed based on a system of MHTGRs. A lumped-parameter model is given for the six-modular MHTGR plant HTR-PM600. A numerical simulation software is developed based on this model. The open-loop and closed-loop responses are shown by simulation.